Penguatan Branding Wisata Desa Kertawangi melalui Edukasi Digital dan Sosialisasi Komunitas - Ahmad Pramegia; Justin Bongsoikrama; Lies Andayani; Aris Wahyu Kuncoro; Yuni Kasmawati; Astrid Dita Meirina Hakim; Teja Endra Eng Tju; Rina Ayu Vildayati; Yuphi Handoko Suparmoko (Pusat Riset dan Inovasi Nasional, 2025)
The Community Service Program (PKM) in Kertawangi Village, Cisarua District, West Bandung Regency, aims to strengthen the village’s tourism branding through digital education and community-based social engagement. The program was implemented using a participatory approach involving residents in installing street name signs, conducting educational activities at the elementary school, providing digital tourism promotion training, and organizing interactive social events. The results show an increase in digital literacy, students’ learning motivation, and community participation in managing local potential. The publication of tourism promotion content on social media has enhanced the village’s visibility as an educational tourism destination. Beyond its physical outputs, the program strengthened social cohesion, local cultural values, and residents’ capacity to utilize information technology. This PKM initiative demonstrates that collaboration between universities and rural communities can foster sustainable empowerment through education and digitalization.